LEGAL COMMENTS IN RELATION TO THE LATGALIAN WRITING LANGUAGE AS A HISTORICAL VARIETY OF LATVIAN - Bitāns, Agris (Via Latgalica, 2012)
The paper is aimed at provision of legal assessment of the Latgalian language as a variant of Latvian, using mainly the analytical and historical method.Notwithstanding the fact that the Official Language Law recognizes that the Latgalian language is a variant of the Latvian language, there is no absolute clarity with regard to the status of this language and its practical use in formal communication. Also the attitude from public authorities is inexcusably inappropriate – as far as declaring the Latgalian language to be a foreign language. However, from historical point of view the Latgalian language was recognised and applied in official communication, including also judicial proceedings, in Latgale.Positive evaluation has to be given to the discussion, which has been opened with regard to the Latgalian language and its legal status. It should be noted with satisfaction, that their significant contribution is provided also by Latvians from other regions, and edition of „Jurista Vārds” („Lawyer’s Word”), dated 25 October 2011, is a good confirmation. However, the practice is indicative that there is no clarity with regard to legal status of the Latgalian language and its practical use in formal communication. Currently existing approach of the approved establishments on Latvia results from historical prejudices and ignorance.Existence of a number of languages as official state languages is nothing exceptional, and also the dialects or vernaculars may be constitutionally protected and their use can be defined. In evaluation of the constitutional framework also in other countries, a conclusion should be drawn that proper normative strengthening and daily use of the Latgalian language constitutes no threat to the official language. On the contrary, it could be a basis for raising confidence in Latgale, as well as in other regions. Linguistic diversity is the national cultural and historical heritage, which is worth a special appreciation and protection.Although nomenclative designation of the Latgalian language (language of Latgale) should be specified, it is much more important to come to understand the content of this concept in order to clearly denote the language, which is spoken not only in the region of Latgale of the contemporary Latvia, but also beyond, preserving for the language its historic roots.The Latgalian language was recognized to be one of the cornerstones in foundation of the Latvian state when the Latvian state was founded, and it was consistently respected also after the Republic of Latvia was proclaimed. In the normative field forgetting or disregarding of the Latgalian language has started to be present only after K. Ulmanis’ coup, while depriving the Latgalian language of its legal status and regulation.With the Official Language Law the Republic of Latvia in a normative way has demonstrated its special attitude towards the Latgalian language. The State has determined not only to protect and at the same time to regulate the Latgalian language, but has assumed even larger active obligation to maintain and to develop the Latgalian language.There are neither legal nor linguistic or logical grounds to declare the Latgalian (Latgale) language (not to say the dialect!) to be a foreign language. The claim that the Latvian literary language is the only one to be recognized as the official language would have to be considered erroneous, because it has no normative basis. Latgalian language meets all requirements for a literary language, i. a., it has approved orthography rules in accordance with the laws and regulations of the Republic of Latvia.Conclusions made by the decision of Senate in case No. A42571907 S–596/2009, dated 18 August 2009, cannot be construed to be legitimate, because these are not only discrepant with legal method, but also clearly contrary to the logic. Declaring the Latgalian language, as well as any dialect to be a foreign language causes great damage to statehood of Latvia, first of all, to the local self-confidence.There is no legal basis to prevent contacts with governmental and local authorities in any vernacular or dialect of Latvian, still less there is a legal basis to limit communication in officially recognised variant of the official language – Latgalian (of Latgale) language.The State in the nearest future should enforce in practice the obligation undertaken by the Official Language Law – „maintenance, protection and development of the Latgalian written language as a historic variant of the Latvian language”. Including practical use of the Latgalian language as a variant of the Latvian language should be ensured in communication with governmental and local authorities in the Republic of Latvia according to the existing law. The State should ensure obligations undertaken by the Official Language Law and should guarantee possibilities to apply to the authorities with a document, drawn up in Latgalian. However, the State should not confine itself only to provision of the document circulation in Latgalian, but it should also carry out a series of other real activities, including allocation of necessary funds from the State budget in order to maintain, to protect and to develop the Latgalian language.